Influence of BNPL Loans and Consumer Motivation on Youth Consumptive Behavior: Evidence from Pungpungan Village, Bojonegoro Regency, Indonesia - Reza Anggapratama; Rina Sulistyowati; Fharhan Hadi Sulthoni; Muhammad Rizqi Agustino; Kustaji; Fauzian Noor (Journal of Management Studies and Development, 2026)
This study aims to investigate the influence of buy-now-pay-later (BNPL) online loans and consumer motivation on the consumptive behavior of youth in Pungpungan Village, Bojonegoro Regency. The collected data were processed quantitatively.This study adopts a correlational research design to examine the relationships between buy-now-pay-later online loan usage, consumer motivation, and the consumptive behavior of youth in Pungpungan Village, Bojonegoro Regency. The final sample comprises 100 respondents. The results indicate that both Pay Later usage and consumer motivation have a positive and significant effect on the consumptive behavior of youth in Pungpungan Village, both individually and simultaneously. Pay Later usage shows a stronger influence (0.485) compared to consumer motivation (0.208), with the model explaining 31.8% of the variance in consumptive behavior. These findings suggest that the ease of deferred payments combined with high consumer motivation substantially drives impulsive and excessive spending among rural youth. This study extends the literature on consumer behavior by integrating buy-now-pay-later (BNPL) usage and consumer motivation as joint predictors of consumptive behavior in a rural youth context. It offers a novel perspective by highlighting how fintech adoption interacts with psychological drivers to shape spending patterns outside urban settings.